An experimental investigation into the most prominent sources of uncertainty in wave tank testing of floating offshore wind turbines. Issue 1 (1st November 2022) - Lyden, E.; Judge, F.; Gueydon, S.; O'Shea, M.; Murphy, J.
Abstract : There is an urgent need to replace carbon-based energy sources with renewable energy sources, and floating offshore wind is seen as a critical component in the drive towards energy diversification. Floating offshore wind facilitates accessing a far vaster wind resource that exists in deeper waters, further offshore. Floating offshore wind platforms must undergo wave tank testing in the early stages of development to assess model responses to different wave and wind conditions. Wave tank testing, while highly beneficial, is liable to have errors arising throughout the testing campaign. Errors can arise during wave tank setup, testing, and analysis of results. One such error is the error in the inertia and centre of gravity (CoG) of the platform. In this research, testing was completed using two very different floating offshore wind concepts. A sensitivity analysis was completed by varying the model inertia and centre of gravity. It was found that the effects of each variation were magnified at resonance, and the magnitude of platform response was affected to a greater extent than the period of resonance response. Of all the variations to the model properties conducted, the inertia about the y-axis and location of the centre of gravity along the x-axis affected pitch response to the greatest extent.